Konsep Pendidikan Akhlak Perspektif Ibnu Qoyyim Al Jauziyyah Dan Bisri Mustofa - Muhamad Akip; Ahmad Taufik (El-Ghiroh : Jurnal Studi Keislaman, 2021)
Islamic education is a human need as a pedagogical creature with the potential to be a caliph on earth. The method used in this paper is descriptive qualitative to describe the Moral Perspective education of Ibnu Qoyyim Al Jauziyyah and Bisri Mustofa and its current relevance. Various facts of Islamic education are not like training that will produce specialists but the process of education to form and direct a good person through habituation. The purpose of education in the view of Ibnu Qayyim tarbiyah is to maintain the purity or purity of human nature. Education given by Ibnu Qayyim and Bisri Mustofa is relevant until now it can restore the meaning of education as tarbiyah, ta'lim, ta'dib and tazkiya in line with Bisri Mustofa, namely nguwonke or humanize humans because in essence the highest knowledge is Morals.